2010
DOI: 10.1021/jf1015285
|View full text |Cite
|
Sign up to set email alerts
|

Black-Tea Polyphenols Decrease Micellar Solubility of Cholesterol in Vitro and Intestinal Absorption of Cholesterol in Rats

Abstract: Administration of black-tea polyphenols (BTP) simultaneously reduced lymphatic recovery of both (3)H-cholesterol and (14)C-trioleoylglycerol in rats that were cannulated in the thoracic duct. BTP decreased the in vitro micellar solubility of cholesterol in a dose-dependent manner. When purified theaflavins, which are components of BTP, were used, theaflavin-monogallates (TFMGs), theaflavin-3-gallate (TF3G), and theaflavin-3'-gallate (TF3'G) were effective in eliminating cholesterol from bile salt micelles in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…The polyphenolic pattern of white, green and black tea extracts have been reported previously (Almajano, Carbó, López Jiménez, & Gordon, 2008;Ikeda et al, 2010;Wu et al, 2012). White and green tea leaves are characterised by higher levels of catechins than black tea, since the postharvest treatments, specifically fermentation, convert these compounds to other higher molecular mass compounds, mainly, theaflavins ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The polyphenolic pattern of white, green and black tea extracts have been reported previously (Almajano, Carbó, López Jiménez, & Gordon, 2008;Ikeda et al, 2010;Wu et al, 2012). White and green tea leaves are characterised by higher levels of catechins than black tea, since the postharvest treatments, specifically fermentation, convert these compounds to other higher molecular mass compounds, mainly, theaflavins ( Fig.…”
Section: Resultsmentioning
confidence: 92%
“…HPLC separation and quantification of phenolic compounds in tea extracts and samples obtained from in vitro digestion, transepithelial permeation, and plasma protein binding experiments, were performed according to earlier studies (Ikeda et al, 2010;Wu, Xu, Héritier, & Andlauer, 2012) with some modifications, as follows. Identification of individual polyphenols was achieved by recording chromatograms at 280 nm and comparison with spectra and retention times for the standards and those reported in the literature.…”
Section: Hplc-dad/esi-ms N Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other works reveal the possibility that oligomeric procyanidins may be effective in reducing plasma cholesterol concentration and suppressing activity on postprandial hypertriacylglycerolemia. Actually, such effects were mainly demonstrated for grape seed, red wine and tea polyphenolic extracts (Leifert & Abeywardena, 2008;Ikeda, Yamahira, Kato, & Ishikawa, 2010;Kobayashi et al, 2009), but no studies reporting such bioactivities for apple procyanidins are available in literature so far.…”
Section: Introductionmentioning
confidence: 97%
“…Compared to micelles without gypenosides, cholesterol in the supernatants obtained after ultracentrifugation decreased, and then it was revealed that gypenosides inhibited the incorporation of cholesterol into mixed micelles. A series of experiments have shown that polyphenol as an approach to a potential reduction in cholesterol absorption was correlated with the inhibitory effect of cholesterol micelle solubility [20,33]. Adisakwattana revealed that grape seed extracts inhibited pancreatic lipase Each measurement was repeated three times, and data are presented as mean ± SD in dose-dependent manner and also inhibited the formation of cholesterol micelles [34].…”
Section: Effects Of Gypenosides On the Cholesterol Micelle Solubilitymentioning
confidence: 99%